1993
DOI: 10.3109/03093649309164362
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gait using a Multiflex foot versus a Quantum foot in knee disarticulation amputees

Abstract: The subjective responses and gait patterns of unilateral knee disarticulation amputees wearing prostheses fitted first with the Multiflex foot and then with the Quantum foot were studied. Nine amputees were included in the trial. A questionnaire asked the amputees about their preference for one of the feet. Gait analysis was performed measuring temporal parameters and goniometry of hips, knees and ankles in the sagittal and frontal planes. There was a slight preference for the Quantum foot. Preference seeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The remaining 98 studies (3 hip, 53 above-knee, and 42 below-knee) reported accommodation times, tested their participants only once, and did not test on the same day of the participants receiving a new limb (Figure 2, Tables 6 and 7). 7,8,10,1319,2124,2639,4150,53,54,57,58,6177,81,82,85,86,88,91,92,94…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 98 studies (3 hip, 53 above-knee, and 42 below-knee) reported accommodation times, tested their participants only once, and did not test on the same day of the participants receiving a new limb (Figure 2, Tables 6 and 7). 7,8,10,1319,2124,2639,4150,53,54,57,58,6177,81,82,85,86,88,91,92,94…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-three of the 156 studies made no comments regarding accommodation or did not provide a justification of a given accommodation time. 5,6,1317,21,2427,33,3537,4042,48,52,54,56,6063,66,75,78,79,8386,91,92,9496,101,103,104,107,109,112115,118,120125,127131,133–138,140,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a reliable and useful measure of functional mobility especially for people with impairment [ 19 ], TTAs included [ 20 ]. In studies of prosthetic components SSWS has often been used as a parameter for the quality of performance [ 21 , 22 ] also when different prosthetic feet were compared [ 23 ]. According to other studies [ 24 ] the average SSWS (m/s) for each participant was computed dividing the covered distance by 360 seconds.…”
Section: Methodsmentioning
confidence: 99%